Workers organizing in the platform economy: Local forms and global trends of collective action - Rafélis de Broves, Olivier; Kang, Minhyoung; Grohmann, Rafael; Barcellos, Victor; Gomes Mano, Felipe [UNESP]; Yoon, Cheolki; Jamil, Rabih (Wiley, 2024)
Distinctive features of the on-demand work platforms made it theoretically improbable for workers to organize and for collective forms of protest to emerge. Their business model and work arrangements spatially isolate and socially individualize workers, subjectivizing them as competing micro-enterprises rather than co-workers. However, faced with the flood of the platforms on a global scale, collective actions of platform workers surged like a backwash, especially in the ride-hailing and food delivery sectors, during the last decade. Observers witnessed a great variety in the combination of actors involved and repertoire of actions mobilized worldwide. Despite this diversity, some common global trends can be sketched out. Through a literature review focused on Europe, Latin America, North America and Asia, this article shows that workers struggle globally to build a collective actor, through an original combination of new and old forms of protest. They ought to compensate for their weak marketplace bargaining power by leveraging their discursive, associational, coalitional and workplace bargaining powers.
Keywords: collective action; food delivery platform; platform economy; ride-hailing platform; workers organizing